2018
DOI: 10.1155/2018/1962832
|View full text |Cite
|
Sign up to set email alerts
|

Durability and Microstructure Properties of Concrete with Arabic Gum Biopolymer Admixture

Abstract: Arabic gum biopolymer (AGB) has recently been demonstrated to improve mechanical and physical properties of fresh and hardened concrete which makes it a promising sustainable and environmentally friendly water-reducing admixture. The present work focuses on the effect of added AGB on the workability, setting time, and durability of concrete. Furthermore, a microstructure analysis is conducted to provide objective evidence and support for previous findings and hypothetic interpretations. Flow table experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The result of slump tests is shown in Table (2) and graphically in Figure (5). Generally, it has been shown that slump increases with increasing GA ratios.…”
Section: Results Of Slump Testsmentioning
confidence: 92%
See 2 more Smart Citations
“…The result of slump tests is shown in Table (2) and graphically in Figure (5). Generally, it has been shown that slump increases with increasing GA ratios.…”
Section: Results Of Slump Testsmentioning
confidence: 92%
“…Also, it was observed that for concrete mixes containing 0.7% of GA dosage the cubes demolding required two days. (5) shows the average compressive strength of the concrete cubes taken at ages of 7, 28 and 91 days. There were large increases in strength when the dosages of GA and curing of samples were increased.…”
Section: Results Of Slump Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in the percentage of water absorption obtained for blocks with GA is explained by the emulsifying property of GA which allows it to fill the voids in the cement microstructure, increase the density of the material and create bonds between different particles thus reducing the voids between the different particles [7,20,34,45]. In addition, [32]confirmed that GA is a stabilizer and waterproofing agent used in mud coatings.…”
Section: 11water Absorption Of Compressed Stabilized Laterite Blocksmentioning
confidence: 86%
“…It is probably because of this high density that these types of blocks showed the lowest percentage of water absorption at 28 days (3.8%) and the highest compressive strength at 28 days (4.23 MPa). This is because the reaction between cement and GA forms calcium silicate hydrate (C-S-H) that is denser and in greater quantity than the C-S-H obtained from cement alone, which further improves the material properties and leads to better performance [34,45]. Dry density results of laterite soil stabilised with GA without cement showed that dry density decreases with increasing GA content [22,50].…”
Section: 12dry Density Of Compressed Stabilized Laterite Blocks With 2% Of Cement and Various Percentages Of Gamentioning
confidence: 99%